THE INFLUENCE COLLABORATIVE DRILL OF INTERCULTURAL COMMUNICATION APPROACH FOR UNDERGRADUATE STUDENT IN ENGLISH LANGUAGE LEARNING - Yuli Marlina; Maryam Sulaeman; Endang Iryani (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2022)
This study applies quantitative research with experimental of nonequivalent control group design. It is aimed to investigate the willingness’ of language study through  collaborative drill of intercultural communication approach in english language study at Universitas Islam Jakarta. The researcher used the collaboratie drill of intercultural communication approach which applied pre-test, treatment and post-test to see the effectiveness of its approach in language learning particularly in English study. The study found that there is significant effect in students’ language learning at Islamic University of Jakarta 73,4% or 0,734. Moreover, in coofficient determination was found that Y variation is  caused by X from the table can be read  in square value (R2) of 0.539. The value of the S(0.555 squared) = 0.539 or 53.9,%. It  means that the variation occurring in English learning process is 53.9% due to the  collaborative drill of intercultural communication  approach and the remaining was 46.1% (100% - 30.8%)it  is used by other variables were not discussed in this study. In  other words the magnitude of effectiveness of  collaborative drill of intercultural communication approach in English learning was 53,9%. In addition, R-test with ro result was 0.734, then the result is bigger than rt significant level 5% that was 0,161 and 1% that was 0,207. Thus it can be seen that ro> rt either at a significant level of 5% or 1%. It can be cconcluded that Ha was accepted and HO was rejected, the meaning it is suspected that there is  significance influence in language study through drill collaborative of intercultural communication approach  for undergraduate student